2020
DOI: 10.2147/rru.s284066
|View full text |Cite
|
Sign up to set email alerts
|

<p>Infiltrating Treg and Th17 Cells of the Prostate Hypertrophy Gland Associated with <em>Propionibacterium Acnes</em> Infection</p>

Abstract: The aim of the study was to evaluate prostate cell infiltration by CD4(+)IL-17(+) and Treg cells in BPH and PCa patients depending on P. acnes infection in the prostate gland. Patients and Methods: Prostate fragments were collected from 54 patients with PCa and 34 patients with BPH. Rapid ID 32 was used to identify the bacteria. Cells were analyzed by flow cytometry BD FACSCanto II. Statistical analysis was performed using Statistica 7 software (TIBCO Software Inc, USA). Results: P. acnes was detected in 35% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…P. acnes has also been shown by Alexeyev O. et al as the predominant microorganism in prostatic tissue in a large cohort of BPH patients [ 32 ]. Other authors also confirmed the high frequency of P. acnes isolation from individuals with BPH (positive P. acnes in 41% of cases) [ 49 ]. Cohen et al observed a significant higher degree of prostatic inflammation in prostate samples positive for P. acnes [ 50 ].…”
Section: P Acnes In Patients With Bph and Pcamentioning
confidence: 54%
“…P. acnes has also been shown by Alexeyev O. et al as the predominant microorganism in prostatic tissue in a large cohort of BPH patients [ 32 ]. Other authors also confirmed the high frequency of P. acnes isolation from individuals with BPH (positive P. acnes in 41% of cases) [ 49 ]. Cohen et al observed a significant higher degree of prostatic inflammation in prostate samples positive for P. acnes [ 50 ].…”
Section: P Acnes In Patients With Bph and Pcamentioning
confidence: 54%
“…The bacterium showcased a wide range of virulence factors, including enzymes such as lipases, proteases, and chemotactic factors for immune cells ( 313 ). Reports also indicate the promotion of innate immune cells, including macrophages which release cytokines such as tumor necrosis factor, Il-1, 6, 8, and 12 ( 27 , 314 , 315 ). By upregulating the vascular endothelial growth factor (VEGF), IL-17 release contributes to the activation of malignant cell proliferation and the production of new blood cells ( 316 ).…”
Section: Chlamydia Trachomatismentioning
confidence: 99%
“…By upregulating the vascular endothelial growth factor (VEGF), IL-17 release contributes to the activation of malignant cell proliferation and the production of new blood cells ( 316 ). Further, the disbalance in IL-17 and regulatory T-cells (Treg) cells in tumors could aggravate oncogenesis by inducing immunosuppression ( 315 , 317 ).…”
Section: Chlamydia Trachomatismentioning
confidence: 99%
“…Studies have shown that blocking IL-17 in mice inhibits the development of prostate cancer[ 112 ]. The imbalance in the proportion of CD4 + and IL-17 + cells and CD4 + Foxp3 + T cells, responsible for regulating Treg cells in the tumor microenvironment, may lead to worsening of the inflammatory process and promote carcinogenesis[ 113 , 114 ]. Treg cells are involved in the suppression of antitumor immune responses[ 115 ].…”
Section: Association Between Th17 Response and Different Types Of Cancermentioning
confidence: 99%